Control Policies for a Single Server System - Balachandran, K. R. (Management Science, 1973)
The paper deals with two parametric control policies for a single service facility when the arrivals are distributed as Poisson and the service durations have a general distribution. The N-policy is to turn on the server (i. e., open the service channel for service) when the queue size reaches the number N and turn him off when the system is empty. The D-policy is to turn on the server when the total work to be done reaches the value D instead. The optimum policies are compared for both the policies when the costs assumed are linear. It is shown that for constant service the optimal policies are equivalent and for exponential service the D-policy is not superior to the N-policy.